Geriatrics Education Team Model Results in Sustained Geriatrics Training in 15 Residency and Fellowship Programs and Scholarship. Issue 4 (29th March 2016) - Denson, Steven; Simpson, Deborah; Denson, Kathryn; Brown, Diane; Manzi, Gabriel; Rehm, Judith; Wessel, Bambi; Duthie, Edmund H.
Abstract : Caring for the growing elderly population will require specialty and subspecialty physicians who have not completed geriatric medicine fellowship training to participate actively in patient care. To meet this workforce demand, a sustainable approach to integrating geriatrics into specialty and subspecialty graduate medical education training is needed. This article describes the use of a geriatrics education team (GET) model to develop, implement, and sustain specialty‐specific geriatrics curricula using a systematic process of team formation and needs assessment through evaluation, with a unique focus on developing curricular interventions that are meaningful to each specialty and satisfy training, scholarship, and regulatory requirements. The GET model and associated results from 15 specialty residency and fellowship training programs over a 4‐year period include 93% curriculum sustainability after initial implementation, more than half of the programs introducing additional geriatrics education, and more than 80% of specialty GETs fulfilling their scholarship requirements through their curriculum dissemination. Win–wins and barriers encountered in using the GET model, along with the model's efficacy in curriculum development, sustainability, and dissemination, are summarized.